Pengaruh Desain Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. PLN Rayon Banjar - Garibaldi, Ganjar; Hayati, Neneng (Banking & Management Review, 2022)
During the COVID-19 pandemic, which was marked by the emergence of a new virus that affected the entire world from the spread of the virus, the impact resulting from the COVID-19 pandemic was to impact human resources within the organization. All employees in companies and agencies must do their work remotely (Work fromHome) in order to minimize transmission of COVID-19. Based on a pre-surveyconducted with the Head of Sub Division of Personnel and General Affairs and several employees of PT. PLN Rayon Banjar, the author found a phenomenon that causes the low performance of employees of PT. PLN Rayon Banjar, namely the workprocess and work results that are not in accordance with the company's expectations and have not been able to realize their work according to what has been determined by the company. The method used in this research is descriptive and verification methods, with data collection techniques through distributing questionnaires as manyas 60 respondents. The test used to test the instrument is a validation test and a reliability test. Data analysis used multiple linear regression, correlation coefficient, and determination coefficient. The results showed that the implementation of work design and work discipline at PT. PLN Rayon Banjar has a significant effect on Employee Performance, with a contribution of 92.7%. Work design and work discipline simultaneously affect employee performance by 68.1%.